Chronic Plantar Ulcer. Surgical Treatment by Capital Osteotomy and Plantar Tibial Sesamoidectomy - Villa Fuertes, Alejandro (Revista Internacional de Ciencias Podológicas, 2010)
We presenta clinical case of a 32 years old patient with a neuropathic ulcer under the first metatarsal head, concretly under the tibial sesamoid on the left foot. After doing conservative treatments as daily healing of the ulcer, the use of metatarsal pads, or metatarsal bars to decrease the pressure, we don’t get good results, and it’s decided to do a surgical treatment. The surgery was realized under local anesthesia without a tourniquet. The surgical’s techniques is a complete Reverdin-Isham osteotomy and partial tibial sesamoidectomy. This minimally invasive surgery techiques cause less soft-tissue trauma. The osteotomy was stabilized by a special dressing to avoid undesirable displacements of the metatarsal head. The patient evolved favorably and the ulcer healed. After surgery, we observe a transfer lesion under second and third metatarsal heads. This complication doesn’t cause simptomatology, but we propose an orthopedic treatment to compensate the alteration. The patient has improved life’s quality and walks without difficulty.